To expand two terms such as these, we can use the method called FOIL (stands for First, Outer, Inner, Last). Here is what I mean:
We have two terms: (x - 2)(x - 1)
We should first multiply the First two terms of each term in order to complete the F stage:
(x)*(x) =

So then, we take the two outer terms and multiply them together to complete the O stage:
(x)*(-1) = -x
So far we have two things that we have calculated; at the end of the FOIL process we will have four.
To keep going with the FOIL, we now multiply the two inner terms to complete the I stage:
(-2)*(x) = -2x
Last but not least, we need to complete the L stage - so we multiply the two last terms of each term:
(-2)*(-1) = 2
Now that we have our four terms, let us add them together and combine like terms:

Since -x and -2x both have the x portion in common and they are added together, we can add them to create one single term:
-x + (-2x) = -3x
So now that we have our terms completed, we can combine into one polynomial equation:

or
Answer:
i think 6x
Step-by-step explanation:
cz we have a variable
9514 1404 393
Answer:
(b) 5, 17
Step-by-step explanation:
You can try the answer choices easily enough.
2 +3×8 ≠ 14
2 +3×5 = 17 . . . . this choice works (5, 17)
2 +3×2 ≠ 20
2 +3×4 ≠ 18
2 +3×10 ≠ 12
__
Or, you can solve the equation:
x + (2 +3x) = 22
4x = 20 . . . . . . . . subtract 2
x = 5 . . . . . . . . . . divide by 4
The numbers are 5 and (22 -5) = 17.
Try this option:
1] P(S)=0.84;
2] P(S or C, but not both)=0.4;
3] P(C)=0.76;
4] P(S∪C)=0.6;
5] P(C, but not S)=0.16;
6] P(S∩C)=1.00.
Hey.
acc'g to the conditions :
Let Catherine has x
and James has 5 + 3x
Then,

Hence
• Catherine has = x = $9,
• and James has = 5 +3x = 5 + 3(9) = $32
Thanks.